Paleobotanical and geological perspective of the biodiversity in Mexico - Cevallos-Ferriz, Sergio R. S.; González-Torres, Enrique A.; Calvillo-Canadell, Laura (Instituto de Ecología, A.C., 2012)
The origin of the extant vegetation and diversity of Mexico has a long history. Possibly the extent of this history is the point where the proposals differ, one states that the history begins in the Cretaceous (ca. 132 my) while other emphasize processes restricted to the Plio-Pleistocene (5.3 my), especially if referring the appearance of extant vegetation. Increased knowledge of the geological evolution of Mexico, and the constant change in physiography, along with the study of fossil angiosperms of the region, generates a clearer concept of how and when life forms differentiated and partnered. A hypothesis that combines geological processes and physiographic changes with the presence of plants and vegetation on the emerged continental parts is presented. It is proposed that existing biodiversity does indeed start ca. 132 million years ago, and although lineages that live in Mexico today can be recognized from this time, it is difficult to place their representants within a family, probably because they may represent members of the stem group. By the Paleogene (65-32 my) families, and even genera, that continue to live in Mexico are more easily recognized, but groups of extinct plants or plants growing today in other regions are still common. Based on the morphological/anatomical approach the Neogene (32-1.8 my) fossil plants resemble more those living naturally in Mexico, but still have important differences supporting the recognition of new species only. If in relatively recent times extant and fossil plants in Mexico seem closer based on their morphology/anatomy, it is to be expected that with the vegetation types a similar process can be recognized. The fossil record suggests that from communities that developed under hot-humid conditions in the Cretaceous, vegetation types with different capabilities to tolerate water stress, and communities that favored cool temperate conditions diverged. The process of divergence apparently occurred at two different times in two different regions. During the Paleogene it affected northern Mexico and during the Neogene it affected central and southern Mexico. Further geological and paleobotanical work will refine this proposal that suggests that changes that enable or constrain biological responses are part of other components of the Earth System.